The hydromechanical behavior of opalinus clay fractures: Combining roughness measurements with computer simulations - Keller, Lukas M. (Frontiers in Earth Science, 2022)
The role of surface roughness of fractures in Opalinus Clay and in rocks in general is relevant in understanding the hydromechanical behavior of fractures. Two different fracture surfaces of shear fractures in the Opalinus Clay were investigated. The fracture surfaces were characterized based on their roughness power spectrum. It was found that slickensides fracture surfaces are near fractal-like up to the longest scale with a fractal dimension Df ~ 2.1 and in the absence of a roll-off region at long wavelengths. In contrast, the glassy fracture surfaces show a roll-off region, which is characteristic of a flat surface with rather small and local topographic height variations. The glassy fracture surface is near fractal like with Df ~ 2.0. The measured roughness power spectra were used to create fracture models to study the behavior of different fracture closure mechanism: i) increasing congruence (matedness), ii) closure by compression and iii) closure by swelling. It turned out that the relationship between permeability and mean aperture depends on the fracture closure mechanism. Concerning closure by compression, the root mean square (rms) value of the aperture (aper) distribution aperrms influences the contact formation behavior, which in turn controls the hydromechanical properties. The lower aperrms is, the lower the fracture compliance. Apart from aperrms, the simulations show that in clay rocks, plastic deformation plays an important role in the closure of fractures by compression. In agreement with the experiments, the simulations predict that the permeability falls below 10% of the initial value at a compressive stress of 5 MPa. The simulations predict that fracture closure by swelling is rather ineffective for confining pressures exceeding ~1 MPa.